Xylanase Production from Trichoderma viride and its Immobilization on the Sea Sands Matrix - Sutrisno Sutrisno; Anna Roosdiana; Suratmo Suratmo (Chemistry Department, The University of Brawijaya, 2018)
The study was aimed to investigate the production and characterization of xylanase from Trichoderma viride by determining the optimum condition of xylanase immobilization using sea sand matrix. The parameters were shaking time variations of 1, 2, 3, 4, and 5 hours and xylanase concentration of 0.5, 1.5, 2.5, 3.5, and 4.5mg/mL. Xylanase was purified by ammonium sulfate using the optimum fraction of 40-80%. The optimum shaking time for immobilization of xylanase was reached in 4 h, and the optimum xylanase concentration was obtained in 4.5 mg/mL, with immobilized xylanase activity of 118.55 µg.g-1.min-1 and adsorbed xylanase amount in sea sand matrix of 20.51 mg. Immobilized xylanase can be used up to 4 times, with the percentage of 62.47%. The surface characterization of immobilized xylanase was conducted using SEM.The FT-IR result obtained peaks at wavenumber 3431.13 and 875.62 cm-1 which indicatedthe existence of N-H bond from enzyme and the sea sand bind with enzyme, respectively.